REDUPLIKASI DALAM BAHASA MANDAR - NFN Nurhayati (Linguistik Indonesia, 2015)
The present paper focuses on reduplication in Mandar language. The data of this studywere gathered through observation and introspective methods, which included listening and getting involved in a conversation, recording, and note taking. The objective of this study is to reveal the forms, functions, and meanings of Mandarese reduplication. The results show that there are four forms of reduplication in Mandar: full reduplication, partial reduplication, reduplication with affixation process, and reduplication in combination with clitics. In Mandarese, reduplicated words can fill in the position of subject, predicate, object, and adverb. Reduplication process can change the meaning of the base words. Reduplicated words are generally plural. Other possible interpretations of reduplicated words are to indicate resemblance, simplicity, repetitive action, intensity, a collection of numbers, reciprocal action, the state of proximity.